2017
DOI: 10.1371/journal.pone.0189264
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of and perception towards cardiovascular disease risk in sub-Saharan Africa: A systematic review

Abstract: IntroductionCardiovascular diseases (CVDs) are the most common cause of non-communicable disease mortality in sub-Saharan African (SSA) countries. Gaps in knowledge of CVD conditions and their risk factors are important barriers in effective prevention and treatment. Yet, evidence on the awareness and knowledge level of CVD and associated risk factors among populations of SSA is scarce. This review aimed to synthesize available evidence of the level of knowledge of and perceptions towards CVDs and risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
143
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 56 publications
21
143
5
3
Order By: Relevance
“…Within controls only 22% had high knowledge score, 68% average and 10% low score (Pearson Chi Square 12.073 and P value 0.002). Similar findings have been reported in other parts of the world [9,17,4]. This finding is alarming because at this stage, patients should be well informed of the disease, in order for them to know how to protect themselves.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Within controls only 22% had high knowledge score, 68% average and 10% low score (Pearson Chi Square 12.073 and P value 0.002). Similar findings have been reported in other parts of the world [9,17,4]. This finding is alarming because at this stage, patients should be well informed of the disease, in order for them to know how to protect themselves.…”
Section: Discussionsupporting
confidence: 82%
“…This study showed that the following factors were independently associated with cardiovascular disease: age, family history of CVDs, smoking, alcohol consumption, hypertension, high blood cholesterol, diabetes mellitus, lack of physical exercise, lack of balanced diet and inability to control weight. These factors have also been identified in several studies that have been conducted across the world [4,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 96%
“…Studies have also shown those who understood English were more likely to engage in protective behaviors. 5 It may be that text messaging is not the most appropriate method for CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge and awareness on risk factors at community level hinders healthy behavior change and uptake of early NCD screening and treatment services [101]. A study in Abuja reported a high prevalence of hypertension among the elderly populations, and majority of whom were unaware about their conditions [102].…”
Section: Lack Of Community Awarenessmentioning
confidence: 99%